Desain Komunikasi Kendali Organisasi Lembaga Dakwah Masjid Pada Masa Pandemi Covid-19 - Fatiha Ardi Hatta (STID Al-Hadid, 2022)
ORGANIZATIONAL CONTROL COMMUNICATION DESIGN AT MOSQUE DAKWAH INSTITUTIONS DURING PPKM LEVEL 3-4 Abstract: This study aims to formulate an organizational control communication design at the mosque's da'wah institution during the PPKM level 3-4. Many organizations in Indonesia have been affected by the Covid-19 pandemic. Mosque da'wah institutions are organizations that have been significantly affected, starting from the reduced number of congregations in mosques, reduced income from infaq and alms and zakat to mosques, and the lack of solidity of mosque administrators. The Indonesian government has launched PPKM levels 1-4 in all cities and districts in Indonesia. The mosque's da'wah institution must be able to adapt to the situation and conditions of the Covid-19 pandemic which makes the situation and conditions uncertain and difficult to predict. The mosque's da'wah institution must formulate a communication design for organizational control, especially mosques located in the tightening area or PPKM level 3-4. This study uses a qualitative methodology to develop a theory of organizational control communication in mosque da'wah institutions during the PPKM level 3-4. The results of this study indicate that the organizational control institution that is most likely to be implemented in the mosque's da'wah institution is conservative control. Concert control is more of an interpersonal approach to organizational management, with a conscious drive. In the PPKM level 3-4 situation, the entire communication process carried out by the head of the mosque's da'wah organization was carried out boldly. If face-to-face is required, the organization must strictly adhere to health protocols.